DS-7250, a Diacylglycerol Acyltransferase 1 Inhibitor, Enhances Hepatic Steatosis in Zucker Fatty Rats via Upregulation of Fatty Acid Synthesis. (April 2018) - Yasuno, Kyohei; Kumagai, Kazuyoshi; Iguchi, Takuma; Tsuchiya, Yoshimi; Kai, Kiyonori; Mori, Kazuhiko
Diacylglycerol acyltransferase 1 (DGAT1) catalyzes the final step in triglyceride synthesis. Since Dgat1 -/- mice fed a high-fat diet (HFD) are resistant to hepatic steatosis, DGAT1 inhibitors are expected to have antifatty liver effects. To evaluate the hepatic effects of DS-7250, a selective DGAT1 inhibitor, vehicle or 10 mg/kg of DS-7250 was administered orally to male Fisher 344 (F344) and Zucker fatty (ZF) rats fed a standard diet or HFD for 14 or 28 days. ZF rats showed slight hepatic steatosis regardless of feeding conditions. DS-7250 exacerbated hepatic steatosis in ZF rats fed an HFD compared with the vehicle control. Hepatic steatosis did not occur in F344 rats fed an HFD, in which systemic exposures of DS-7250 were comparable to those in ZF rats. There was a higher expression of genes involved in lipid uptake and fatty acid synthesis in ZF rats compared to F344 rats under HFD conditions. DS-7250 upregulated key genes involved in de novo lipogenesis, which causes hepatic steatosis independently of DGAT1, in ZF rats fed an HFD compared with the vehicle control. These data suggest that ZF rats were more susceptible to hepatic steatosis due to their genetic characteristics and DS-7250 exacerbated hepatic steatosis independently of DGAT1.